Ayurvedic Management of Katigraha (Lumbar Spondylosis): A case study (AYUSHDHARA, 2025)
Among the various causes of low back ache lumbar spondylosis is one of the degenerative spine diseases. Lumbar Spondylosis (Katigraha) is an important clinical, social, economic and public health problem affecting the population worldwide. About 39% of population present complaints of low back ache between 40 to 80 years of age. The clinical manifestations of Lumbar spondylosis are low back pain, stiffness, weakness and intensity of pain more during hyperextension of spine which can be correlated with Katigraha in Ayurveda. In this study patient with complaints of pain in lower back with morning stiffness and the intensity of pain increased after daily workouts approached to the Kayachikitsa OPD. The treatment plan was Panchakarma therapy Katibasti followed by Patrapinda sweda for 15 days along with Shaman chikitsa for a period of 1 month. Following this protocol, the patient got approximately 75% relief in all sign and symptoms. There was reduction in ODI (Oswestry disability index) and improvement in SLR and other physical examinations. Based on the case study, it can be concluded that Katibasti followed by Patrapinda sweda along with Shaman therapy is effective in the management of Katigraha (lumbar spondylosis).